2019
DOI: 10.1021/acs.orglett.9b04345
|View full text |Cite
|
Sign up to set email alerts
|

p-Anisaldehyde-Photosensitized Sulfonylcyanation of Chiral Cyclobutenes: Enantioselective Access to Cyclic and Acyclic Systems Bearing All-Carbon Quaternary Stereocenters

Abstract: The photosensitized p-anisaldehyde-mediated addition of sulfonylcyanides onto the π-system of cyclobutenes is shown to afford highly functionalized cyclobutanes in high yields and diastereocontrol. The homochiral cyclobutene precursors are accessible on multigram scale in two steps through an asymmetric [2 + 2] cycloaddition/vinyl thioether reduction sequence. The enantiopure cyclobutylnitriles can be elaborated further through SmI2-mediated ring opening or converted into new enantiopure cyclobutenes through b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…In more detail, a solution of cis-piperylene (61) in benzene in the presence of various carbonyl compounds was irradiated using a Hanovia quartz immersion reactor. It was shown that compounds that had a triplet state energy of 70 kcal/mol or more produced photostationary mixtures of a trans/cis ratio of ≈1.25.…”
Section: Aldehydes As Photoinitiators In Organic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In more detail, a solution of cis-piperylene (61) in benzene in the presence of various carbonyl compounds was irradiated using a Hanovia quartz immersion reactor. It was shown that compounds that had a triplet state energy of 70 kcal/mol or more produced photostationary mixtures of a trans/cis ratio of ≈1.25.…”
Section: Aldehydes As Photoinitiators In Organic Synthesismentioning
confidence: 99%
“…In 2020, Landais and co-workers developed a photosensitized sulfonylcyanation of chiral cyclobutenes [61]. Although cyclobutanes are substrates of significant pharmaceutical use, the unsaturated analogs, cyclobutenes, are characterized by a Scheme 38: Substrate scope for the photochemical addition of aldehydes to Michael acceptors.…”
Section: Aldehydes As Photoinitiators In Organic Synthesismentioning
confidence: 99%
“…Photocatalyzed sulfonyl-cyanation of cyclobutenes 25 a-c using p-anisaldehyde as a photosensitizer, [22,27] was then shown to proceed in excellent yield. The reaction applied to cyclobutene 25 c thus delivered the desired cyclobutyl nitrile 26 c in 72 % yield and d.r.…”
Section: Resultsmentioning
confidence: 99%
“…Landais and coworkers used p-anisaldehyde as photosensitizer in the sulfonylcynation of chiral cyclobutenes (Scheme 7). 18 The reaction showed high efficiency when compared to the use of other organic dyes. Moreover, excellent diastereoselectivities were observed in these reactions.…”
Section: Photo-organocatalytic Reactionmentioning
confidence: 97%